2023
DOI: 10.1158/1078-0432.c.6527757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data from Noninvasive Detection of Microsatellite Instability and High Tumor Mutation Burden in Cancer Patients Treated with PD-1 Blockade

Abstract: <div>AbstractPurpose:<p>Microsatellite instability (MSI) and high tumor mutation burden (TMB-High) are promising pan-tumor biomarkers used to select patients for treatment with immune checkpoint blockade; however, real-time sequencing of unresectable or metastatic solid tumors is often challenging. We report a noninvasive approach for detection of MSI and TMB-High in the circulation of patients.</p>Experimental Design:<p>We developed an approach that utilized a hybrid-capture–based 98-k… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Additionally, other methods such as the tumor mutation burden (TMB)-which works on the basis of the potential for mutations in tumors to generate immune triggering neoantigens-have also been utilized to predict the response of cancer patients towards ICBs [18,19]. In these studies, it was demonstrated that the TMB method accurately predicted the response rate of cancer patients in cancer types with high tumor mutation burden (TMB-H), such as lung cancer, bladder cancer and melanoma with an objective response rate (ORR) of 39.8% (95% confidence interval; CI: 34.9-44.8) [18].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, other methods such as the tumor mutation burden (TMB)-which works on the basis of the potential for mutations in tumors to generate immune triggering neoantigens-have also been utilized to predict the response of cancer patients towards ICBs [18,19]. In these studies, it was demonstrated that the TMB method accurately predicted the response rate of cancer patients in cancer types with high tumor mutation burden (TMB-H), such as lung cancer, bladder cancer and melanoma with an objective response rate (ORR) of 39.8% (95% confidence interval; CI: 34.9-44.8) [18].…”
Section: Introductionmentioning
confidence: 99%